Membangun Literasi Informasi melalui Budaya Baca Masyarakat (Pustakaloka, 2010)
The obvious sign of global era is information availability throughout the world. Therefore, everyone must become a literate person to reacha better life. Because life is personal progressive, every person shoould change and renew his personal quality to keep away from extinction. Besides, it is also influenced by many factors, such as cultural and structurl factors. however, nowadays we see a fact of lower reading habit that can effect on information literacy. For that reason, an effort to increase a higher reading habitÂ  can be performed by three strategies, i.e. power strategy, persuasive strategy and normative-reeducaritve strategy.